Comparative efficacy of Levofloxacin and Prulifloxacin against Uropathogenic Escherichia coli and Klebsiella spp. from a tertiary care hospital and their correlation with expression of lipase and lecithinase - S, Bhattacharyya; S, Kumari; A, Sarfraz; NK, Jaiswal; R, Kumar; S, Singh; A, Kumar; A, Sengupta; D, Kumar (Eastern Journal of Medical Sciences, 2016)
Background: Fluoroquinolone antibiotics are often used for treatment of urinary tract infections. Prulifloxacin is a newer fluoroquinolone antimicrobial, and a prodrug of Ulifloxacin. It has been approved for use in Urinary tract infections and respiratory tract infections in many countries, but comparative studies comparing its efficacy against that of Levofloxacin are rare. Objectives: Our study aimed at studying this comparative efficacy. Methods: E. coli and Klebsiella spp. were isolated and identified from urine samples and their antibiogram was seen in respect to Levofloxacin and Prulifloxacin by Diak diffusion method. Antibiogram results were correlated with lecithinase, lipase and protease activities of the bac teria. Results: Most of the E. coli isolates were resistant to Prulifloxacin, but is was mostly effective against Klebsiella spp. Conclusion: Prulifloxacin is not a good option for empirical treatment of urinary tract infection, especially those caused by E. coli.